1919
DOI: 10.2105/ajph.9.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Spore-Bearing Ærobic Gas-Forming Bacillus in Baltimore City Drinking Water

Abstract: In a paper that has the additional merit of brevity Mr. Ewing goes direct to his point, tells what he has seen and suggests that weather may be related to results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1924
1924
1929
1929

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A Gram negative spore-forming anaerobic bacillus giving gas in lactose was isolated by Meyer (24). Ewing (25) was able to isolate a similar organism which gave false results. Hinman (26) found that 80 per cent of the positive tests given in lactose broth were not due to members of the colon group.…”
Section: False Presumptive Testsmentioning
confidence: 99%
“…A Gram negative spore-forming anaerobic bacillus giving gas in lactose was isolated by Meyer (24). Ewing (25) was able to isolate a similar organism which gave false results. Hinman (26) found that 80 per cent of the positive tests given in lactose broth were not due to members of the colon group.…”
Section: False Presumptive Testsmentioning
confidence: 99%